TRIB3 facilitates glioblastoma progression via restraining autophagy - Tang, Zhanbin (Aging (Albany NY), 2020)
The pseudokinase Tribble 3 (TRIB3) is known as a regulator in cellular responses to a variety of stresses, such as glucose insufficiency and endoplasmic reticulum (ER) stress. TRIB3 is upregulated in various cancer tissues and is closely connected to the poor prognosis of patients. However, the underlying regulation and function of TRIB3 in glioblastoma (GBM) is still largely unknown. In this study, the upregulation of TRIB3 was confirmed both in primary specimens from GBM patients and in vitro with GBM cell lines. Overexpression of specific TRIB3 transcripts promoted cell growth and migration in vitro, while knockdown of TRIB3 expression exerted a repressive effect on these cellular processes. The growth-promoting effect of TRIB3 was also demonstrated in a xenograft mouse model. Mechanistic studies further revealed that TRIB3 was able to suppress autophagic flux and that this suppression was responsible for TRIB3 silencing-induced proliferation and migration of GBM cells. These findings indicate that the suppression of autophagic flux by TRIB3 drives the invasion and proliferation of GBM cells, thus suggesting that TRIB3 is a potential novel therapeutic target for the treatment of glioma.